Primary Carcinosarcoma of the Pancreas With CD10-Positive Sarcoma Component - Christine J. Salibay DO; Julia Rewerska MD; Shweta Gupta MD, FACP; Nicholas Ree DO (SAGE Publishing, 2017)
Carcinosarcomas of the pancreas are rare entities with a dismal prognosis. We report a rare case of pancreatic carcinosarcoma in a 49-year-old African American female who underwent a total abdominal hysterectomy with right salpingo-oophorectomy and exploration of the pancreatic mass. The surgery revealed a sclerotic mass in the body and tail of the pancreas that was surgically unresectable, and a pancreatic biopsy confirmed the pathology of pancreatic carcinosarcoma. Histologically, the lesion showed a high-grade spindle cell sarcoma and adjacent moderately differentiated adenocarcinoma. On immunohistochemical examination, the carcinomatous component was positive for epithelial markers, and the sarcomatous component was focally positive for SMA and desmin. In addition, the sarcomatous component showed diffuse immunoreactivity for CD10 with a surrounding myofibroblastic proliferation. Reports have associated expression of CD10 in pancreatic stellate cells with increased tumor aggressiveness. In this article, we report a case of pancreatic carcinosarcoma that shows sarcomatous CD10 immunoexpression with higher Ki67 labeling in the sarcoma than the carcinoma raising the question if the sarcomatous component could be potentiating the aggressiveness of the carcinomatous component.